Hashimoto’s Thyroiditis in a Female Adolescent: A Case Report (Dhaka Shishu (Children) Hospital Journal, 2026)
Hashimoto’s thyroiditis is the leading cause of acquired hypothyroidism in children, with growth delay often being the earliest sign. We report a 12-year-old girl presenting with short stature, sluggishness, alopecia, constipation, dry skin and acanthosis nigricans. Thyroid tests showed markedly elevated TSH and low free T3 and free T4, while thyroid autoantibodies were positive, confirming Hashimoto’s thyroiditis. Thyroid ultrasound was normal. Levothyroxine 50 μg/day was initiated. After six months, the patient showed significant improvement with resolution of symptoms, normalization of thyroid function, a 7.5-cm height gain and a 4-kg weight loss. This case highlights the need for early recognition of hypothyroidism in adolescents presenting with growth delay and nonspecific symptoms.DS (Child) H J 2024; 40(1): 56-59